FISABILILLAH ERA KONTEMPORER DALAM PERSPEKTIF RASYID RIDHA - Nurhasanah; Arfah; Fitriana (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2024)
This research discusses Muhammad Rasyid Ridho's views on fisabilillah in the contemporary era, where in classical jurisprudence studies and tafsir asnaf fisabilillah is interpreted as a person who strives or fights to defend the religion of Allah, apart from that his zakat funds may only be intended for these people (asnab eight) and may not be allocated to others. This research is a library research type using qualitative methods. In his book Tafsir Al-manar volume 10, Rasyid Ridho explains that fisabilillah is for the benefit of Muslims, through which all sharia and daulah activities run, not for individual interests. In this way, everything related to the benefit of the Muslims can be used from this stock, if there is no such asnab, then it may be allocated to another asnab. What is the basis of his views in this case is based on the situation of Muslims which is increasingly sad at the moment, both in terms of religion, society and educational backwardness.